2019
DOI: 10.1016/j.ajhg.2018.12.016
|View full text |Cite
|
Sign up to set email alerts
|

TBC1D8B Loss-of-Function Mutations Lead to X-Linked Nephrotic Syndrome via Defective Trafficking Pathways

Abstract: Steroid-resistant nephrotic syndrome (SRNS) is characterized by high-range proteinuria and most often focal and segmental glomerulosclerosis (FSGS). Identification of mutations in genes causing SRNS has improved our understanding of disease mechanisms and highlighted defects in the podocyte, a highly specialized glomerular epithelial cell, as major factors in disease pathogenesis. By exome sequencing, we identified missense mutations in TBC1D8B in two families with an X-linked early-onset SRNS with FSGS. TBC1D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 30 publications
3
34
0
Order By: Relevance
“…For example, (1) missense mutations of TBC1D8B have been identified in cases of an X-linked early-onset steroid-resistant nephrotic syndrome. In podocyte cell models, mutated TBC1D8B results in defective trafficking pathways [ 52 ]; (2) more than 50 mutations of TBC1D24 are now associated with a range of inherited neurological disorders, including myoclonic epilepsy, epileptic encephalopathy, and the DOORS syndrome (deafness, onychodystrophy, osteodystrophy, mental retardation, and seizures). Additionally, the cellular functions of TBC1D24 are involved in regulating the small GTP-binding protein, ARF6 [ 9 , 53 , 54 ]; (3) truncating mutations in TBC1D23 are responsible for a form of pontocerebellar hypoplasia, by affecting dense core vesicles and lysosomal trafficking dynamics [ 55 ]; and (4) mutated TBC1D20 has been identified in 77 families affected by the Warburg micro syndrome, which is characterized by eye, brain, and endocrine abnormalities [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, (1) missense mutations of TBC1D8B have been identified in cases of an X-linked early-onset steroid-resistant nephrotic syndrome. In podocyte cell models, mutated TBC1D8B results in defective trafficking pathways [ 52 ]; (2) more than 50 mutations of TBC1D24 are now associated with a range of inherited neurological disorders, including myoclonic epilepsy, epileptic encephalopathy, and the DOORS syndrome (deafness, onychodystrophy, osteodystrophy, mental retardation, and seizures). Additionally, the cellular functions of TBC1D24 are involved in regulating the small GTP-binding protein, ARF6 [ 9 , 53 , 54 ]; (3) truncating mutations in TBC1D23 are responsible for a form of pontocerebellar hypoplasia, by affecting dense core vesicles and lysosomal trafficking dynamics [ 55 ]; and (4) mutated TBC1D20 has been identified in 77 families affected by the Warburg micro syndrome, which is characterized by eye, brain, and endocrine abnormalities [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Supporting the significance of our findings, mutations of TBC1D8B were also reported most recently in two families with SRNS and X-linked inheritance. 64 TBC1D8B Specifically Binds Active RAB11A and RAB11B and the Mutations from Patients with Nephrotic Syndrome Affect Interaction with Endogenous RAB11 TBC1D8B is a member of a family of more than 40 TBCproteins that share the eponymous Tre-2-Bub2-Cdc16 (TBC) domain. 65 This domain commonly confers a functional role as a GTPase-activating protein (GAP) for specific Rab-GTPases, the master regulators of vesicular trafficking including endocytosis.…”
Section: Novel Mutations In Tbc1d8b Cause Snrsmentioning
confidence: 99%
“…We have previously demonstrated that proteins critical for clathrin-mediated endocytosis -dynamin 1 and 2, synaptojanin1, and endophilin -are also critical to maintaining the glomerular filtration barrier (1). Recently, endocytic pathways have been implicated in human proteinuric diseases through identification of genetic mutations in GAPVD1, ANKFY1, and TBC1D8B (2,3). To further investigate clathrin-mediated endocytosis in human disease, in this study we mined the Nephroseq v5 transcriptomic database.…”
Section: Introductionmentioning
confidence: 99%